PENGARUH PSIKOLOGIS SELAMA WFH TERHADAP PRODUKTIVITAS KERJA PUSTAKAWAN DI LINGKUNGAN PDDI-LIPI - Rulina Rachmawati; Yupi Royani (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2021)
Purpose. This study aims to determine the psychological effects during WFH on librarians’ productivity in the Center for Scientific Data and Documentation (PDDI LIPI). Method. The study began by analyzing the demographic characteristics of librarians, librarians’ psychological condition, and librarians’ productivity during WFH. The study used a quantitative method with questionnaires using a Likert scale. The population data were all PDDI librarians who work in Bogor, Cibinong, Jakarta, Serpong and Bandung. The questionnaires were distributed via Google Form to 45 respondents selected by purposive sampling. In order to find out more about the respondent's response to the research topic and questionnaire questions, semi-structured interviews with 5 respondents from each level of librarian position were also conducted. Questionnaire data were analyzed in descriptive statistics, and the correlation between psychological effects during WFH on librarians’ productivity was analyzed using SPSS software and simple linear regression equation. Results and Discussion. The results of the study on librarians’ psychology during WFH suggests that communication and social interaction via online media helps reduce loneliness and facilitate coordination in completing work targets. During WFH, librarians have sufficient time to rest, as a result they do not experience sleep disturbances or feel tired from their daily routine. Sports and hobbies are beneficial for their mental health. Regarding the productivity of LIPI librarians during WFH, most librarians are motivated, comfortable with the workplace they have, able to make structured planning activities, do not have trouble during WFH, and able to achieve the quality work targets. Overall, there is a positive influence between the psychological effects during WFH and the productivity of LIPI librarians even though the correlation between the two is weak. This suggests that there are other factors that affect librarians’ productivity apart from psychological conditions during WFH. In order to maintain the psychological condition and productivity of LIPI librarians during WFH, the policy should be followed up with regular communication and monitoring from management to subordinates to control the librarians’ work targets. Psychological support such as trust from the leaders is necessary as it greatly controls the effectiveness of working remotely and the balance between work and personal life of the librarians.